The risks and opportunities of free trade agreements for progressive labour law reform: the case of the TPP. (2nd January 2021) - Harré, Laila
ABSTRACT: This paper was originally presented as a keynote speech to the AIRAANZ 2020 Conference in Queenstown, New Zealand. By way of background, it was delivered in the context of New Zealand's continued pursuit of multilateral and bilateral trade and investment agreements. The most recent of these is the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), involving New Zealand and 10 other countries in the Asia Pacific region. Such agreements now impose or remove rules well beyond the traditional realm of trade. For example, they incorporate chapters on services, investment, competition, and intellectual property rights protection, and make deep inroads into local regulatory freedom regarding digital development and government procurement. For decades, the treatment of labour standards in the context of globalisation has been debated, both between and within the north and the south, and the labour movement and free trade adherents. What might be called the 'settled centre' of this discussion, has been the inclusion of provisions in these agreements purporting to recognise and encourage the application of selected labour standards. In this paper, the writer assesses the risks and opportunities of agreements like the CPTPPA for progressive labour law reform and argues for alternatives.